Perubahan Kadar Air dan Daya Hantar Listrik Benih Kelapa Sawit (Elaeis guineensis L.) Selama Penyimpanan Periode Pendek dengan Kemasan Polypropylene dan Plastik Vakum pada Kondisi Ruang AC - Mohamad Arif; Endah Retno Palupi (Jurnal Penelitian Kelapa Sawit, 2020)
Factors which influence decline in seed vigor during storage are temperature and humidity in the storage room, as well as utilized storage medium. This study was aimed to obtain information on the effect of different storage media on its ability to maintain moisture content (MC) and electrical conductivity (EC) of oil palm seeds in an AC controlled storage condition. The study was conducted using complete randomized design with single factor, i.e. storage medium with three levels: single polypropylene (PP) plastic (M1), double PP (M2), and vacuum plastic (M3). Results of the experiment showed that the AC controlled condition caused decreases in seed MC at different rates between treatment levels where measured water loss was 11.47% on M3, higher than those of M1 (8.13%) and M2 (6.18%). Even though the three levels indicated decreases on seed MC, the final MC (13.8%) was still higher than that which is allowed (10-12%) for oil palm seed storage, as EC value (2,69 – 3,04 µS.cm-1.g-1) at the end of the trial. For short period (104 d) storage, both parameters showed positive correlation with 0.77 coeffsien of correlation value.